Expanding the Dimensions of a Small, Two-Dimensional Diffraction Detector. (October 2020) - Chen, Xi; Hauwiller, Matthew R.; Kumar, Abinash; Penn, Aubrey N.; LeBeau, James M.
Abstract: Abstract : We report an approach to expand the effective number of pixels available to small, two-dimensional electron detectors. To do so, we acquire subsections of a diffraction pattern that are then accurately stitched together in post-processing. Using an electron microscopy pixel array detector (EMPAD) that has only 128 × 128 pixels, we show that the field of view can be expanded while achieving high reciprocal-space sampling. Further, we highlight the need to properly account for the detector position (rotation) and the non-orthonormal diffraction shift axes to achieve an accurate reconstruction. Applying the method, we provide examples of spot and convergent beam diffraction patterns acquired with a pixelated detector.